Optimización del proceso de elaboración de galletas utilizando harina de coronta de maíz morado (Zea mays L.) - Chavarri Huacacolque, Patricia Belen (2019)
In the present work, the objective was to develop a cookie based on purple corn crown where the parameters of purple corn crown flour and baking time were determined to obtain greater general acceptability. The rotational central composite design (DCCR) was used, carrying out a total of 11 experimental trials with substitutions, of purple corn maize flour between 3 and 7%, and baking time between 8 and 22 min at a temperature of 145 ° C. It was concluded that a lower substitution of purple corn maize flour and not very long baking time results in greater general acceptability. In order to obtain general acceptability between 8 to 10 points, substitutions of purple corn coronta flour between 4.5 to 5.5% and baking time between 13 to 17 minutes would have to be used.